Optimization of carbide tool performance under dry conditions in turning titanium alloy Ti-6A-4V ELI - Adam, Muhamad Alif (2023)
The purpose of this research was to look into the tool life performance of uncoated carbide under dry settings, to find the best parameters for carbide tool performance under dry conditions, and to investigate the tool wear behavior under dry conditions. The notion of tool life is regarded to be the cutting time necessary for a tool to achieve its tool life standards. In this study, uncoated tungsten carbide inserts (CNGG 120408-SGF H13A) will be employed to convert workpiece titanium alloy Ti-6AL-4V ELI (extra low interstitial). Titanium alloys have been widely employed in a wide range of applications, including aerospace, automotive, medical, and chemical sectors. This is owing to the high strength-to-weight ratio, strong fracture resistance, and improved corrosion resistance of titanium alloy. Titanium alloys, on the other hand, are challenging materials to produce even at high temperatures. It has a low elastic modulus, a low heat conductivity and is readily chemically reacted with the material of cutting implements. Based on previous research (Shafi’e, 2017), a two-level Factorial design was utilized to arrange the cutting parameters of 100 to 140 m/min cutting speed, 0.15 to 0.20 mm/rev feed rate, and constant depth of cut (0.35 mm). The progression of flank wear will be monitored using an optical microscope. The data will be collected for each 20 mm of the workpiece until flank wear (Vb) reaches the tool life criterion, at which time they will be replaced (International Standard ISO 3685). As an expected result, maximum tool life (3.97 minutes) is achieved during dry machining at a cutting speed of 100 m/min and a feed rate of 0.15 mm/rev.